Do Coupons Expand or Cannibalize Revenue? Evidence from an e-Market - Reimers, Imke; Xie, Claire (Chunying) (Management Science, 2019)
Coupons have been a mainstay of marketing for decades all over the world, but their short- and long-run effects on sales are still not understood fully. We develop a model of consumer demand to empirically study whether firms can indeed use coupons as a means to price discriminate by attracting new consumers without losing (cannibalizing) revenue from existing ones, and whether these new consumers return to the firm after the price promotion. In addition, we ask what types of businesses are most likely to benefit from such promotions. Following alcohol revenue for restaurants using e-coupons, we find that offering a coupon increases demand during the promotion, and to a lesser degree after the promotion, suggesting that coupons can be used to price discriminate, while an advertising effect is less obvious. While coupons increase profits on average, the effect on each firm’s profits depends on the firm’s characteristics. Data and the online appendix are available at https://doi.org/10.1287/mnsc.2017.2934 . This paper was accepted by Matthew Shum, marketing.